Estudo da síntese da chalcona 1(4’-n-fenil-sulfonilamidafenil)-3-(4-metilfenil)-2epropen-1-ona - (:unkn) unknown (Universidade Estadual de Goiás, 2008)
Malaria is one of the most important infectious diseases in tropical coutries, presenting yearly more than 275 million new cases surge in the word. The control of the disease is limited by development of the resistance by parasite to the drugs used in the treatment, such as chloroquina and quinona, mainly in the most virulent form caused by plasmodium falciparum. One of the aspects that took to the study of sulfonamide-type chalcone as possible antimalarial drug is due to the fact that several studied biological agents attribute this antimalarial activity to sulfonamide like compounds. In this work was study the synthesis of chalcone 1 (4' – n-phenylsulfonylamidephenyl) -3 - (4-methylphenyl) -2-propen-1- one by claisen-schmidt condensation between 4' - n (phenylsulfonylamide) acetophenone (intermediate product) and p-methyl benzaldehyde, using naoh in solution (homogeneous catalysis) and a sample mg and al mixed oxide (heterogeneous catalysis) as catalyst. The hydrotalcite and mixed oxide samples were submitted to physic-chemical analyses. The results shown that both samples are present the typical characteristics of these materials. The intermediate product was synthesized by ultrasound agitation warm to 333 k for 6 hours with yield of 68%. The chalcone was synthesis under magnetic agitation for 6 hours to 353 k ix with yield of 35%. in the reaction effectuated in heterogeneous phase did not obtain the reaction product. The purity of the intermediate product was measured by gas chromatograph and the one of the chalcone by fine layer chromatograph. The analyses by 13c rmn, 1h rmn and iv of the intermediate product and the chalcone showed it was obtained the expected product.
Keywords: Catálise Homogênea; Catálise heterogênea; Condensação de Claisen-Schmidt; Hidrotalcitas; Synthesis of chalcone; Malária; Síntese da chalcona; Chalcona; CIENCIAS EXATAS E DA TERRA::QUIMICA